Lactoferrin: neuroprotection against Parkinson's disease and secondary molecule for potential treatment - Eker, Furkan; Bolat, Ecem; Pekdemir, Burcu; Duman, Hatice; Karav, Sercan (Frontiers in Aging Neuroscience, 2023)
Parkinson's Disease (PD) is the second most common neurodegenerative disease and is largely caused by the death of dopaminergic (DA) cells. Dopamine loss occurs in substantia nigra pars compacta and leads to dysfunctions in the motor functions. Death of DA cells can occur with oxidative stress and dysfunction of glial cells by Parkinson-related gene mutations. Lactoferrin (Lf) is a multifunctional glycoprotein that is usually known for its presence in milk, but recent research shows Lf is also found in the brain regions. MPTP is a known mitochondrial toxin that disturbs the mitochondrial electron transport chain (ETC) system and increases the rate of reactive oxygen species. Lf's high affinity for metals decreases the required iron for the Fenton reaction, reduces the oxidative damage on DA cells caused by MPTP, and increases their surveillance rate. Several studies also investigated Lf's effect on neurons that are treated with MPTP. The results pointed out that Lf's protective effect can also be observed without the presence of oxidative stress, thus several potential mechanisms are currently being researched, starting with potential HSPG-Lf interaction in the cellular membrane of DA cells. The presence of Lf activity in the brain region also showed that lactoferrin initiates receptor-mediated transcytosis in the blood brain barrier (BBB) with the existence of lactoferrin receptors in the endothelial cells. The existence of Lf receptors both in endothelial cells and DA cells created the idea of using Lf as a secondary molecule in the transport of therapeutic agents across BBB, especially in nanoparticle development.